Investigation of the Antiangiogenic Properties of Zoledronic Acid by Using Chorioallantoic Membrane Model - Anil Gulcu MD; Ozgur Akkaya MD (SAGE Publishing, 2022)
Objective Zoledronic acid (ZA) is a bisphosphonate-derived agent used in osteoporotic clinical pathologies to prevent the development of complications such as fractures and hypercalcemia by regulating bone metabolism. Studies have been conducted on the antiangiogenic efficacy of this agent, which also has other systemic side effects. In this study, the dose-dependent antiangiogenic activity of ZA was investigated on the chorioallantoic membrane model (CAM). Methods Three doses (10 −4 , 10 −5 , and 10 −6  M concentrations) of drug pellets were prepared with ZA and another pellet was prepared as the positive control group with vascular endothelial growth factor (VEGF) inhibitor agent bevacizumab (10 −6  M concentration). Thereafter all pellets were placed on chorioallantoic membranes on the fourth day of egg incubation. All eggs were evaluated for capillary development four days after the drug application. Results The highest antiangiogenic effect was detected in the positive control group. Moreover, incremental antiangiogenic effects were detected with average scores of .9, 1.1, 1.2 in 10 −6 , 10 −5 , and 10 −4  M concentrations of ZA groups respectively. Conclusion Our findings supported that ZA has dose-dependent antiangiogenic effects. This result suggests that different dosing may be required in cases where angiogenesis is therapeutic.